Price and non-price competition in oligopoly: An analysis of relative payoff maximizers - Hamed M. Moghadam (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Do firms under relative payoffs maximizing (RPM) behavior always choose a strategy profile that results in tougher competition compared to firms under absolute payoffs maximizing (APM) behavior? In this paper we will address this issue through a simple model of symmetric oligopoly where firms select a two dimensional strategy set of price and a non-price variable known as quality simultaneously. In conclusion, our results show that equilibrium solutions of RPM and APM are distinct. We further characterize the comparison between these two equilibrium concepts. In particular, RPM does not always lead to stricter competition compared to the Nash equilbrium (APM). In fact, the comparison between two equilibrium concepts is influenced by the parameters of demand curve and cost function. The conditions, derived in this paper, determine under which circumstances RPM induces more competition or less competition w.r.t the price or non-price dimension. – – Wählen Firmen, die ihre relativen Profite maximieren (RPM), immer ein Strategieprofil, das zu härterem Wettbewerb führt, im Vergleich zu Firmen, die ihre absoluten Profite maximieren (APM)? In diesem Aufsatz werden wir diese Frage durch ein einfaches, symmetrisches Oligopol-Modell beleuchten, wo Firmen gleichzeitig eine zwei-dimensionale Strategie wählen, bestehend aus einer Preis- und einer nicht-Preis-Variable, die wir als Qualität bezeichnen. Unsere Ergebnisse zeigen, dass die Gleichgewichtslösungen für RPM und APM unterschiedlich sind. Desweiteren charakterisieren wir den Unterschied zwischen diesen beiden Gleichgewichten. Insbesondere führt RPM nicht immer zu härterem Wettbewerb im Vergleich zum Nash-Gleichgewicht (APM). In der Tat wird der Unterschied zwischen den beiden Gleichgewichtskonzepten durch die Parameter der Nachfragekurve und der Kostenfunktion beeinflusst. Die in diesem Aufsatz abgeleiteten Voraussetzungen legen fest, unter welchen Umständen RPM mehr oder weniger Wettbewerb in Bezug auf die Preis- oder nicht-Preis-Dimension induziert.
Keywords: C73; D21; D43; L13; L15; 330; relative payoff s maximizing (RPM); quality; price; oligopoly